Emerging role of different DNA methyltransferases in the pathogenesis of cancer - Liu, Pengcheng; Yang, Fan; Zhang, Lizhi; Hu, Ying; Chen, Bangjie; Wang, Jianpeng; Su, Lei; Wu, Mingyue; Chen, Wenjian (Frontiers in Pharmacology, 2022)
DNA methylation is one of the most essential epigenetic mechanisms to regulate gene expression. DNA methyltransferases (DNMTs) cast a vital role in DNA methylation in the genome. In mammals, DNMTs act with some elements to regulate the dynamic DNA methylation patterns of embryonic and adult cells. Conversely, the aberrant function of DNMTs is frequently the hallmark in judging inflammation and cancer, including total hypomethylation and partial hypermethylation of tumor suppressor genes (TSGs), which improve the malignancy of tumors, aggravate the ailment for patients, and significantly exacerbate the difficulty of cancer therapy. Since DNA methylation is reversible, currently, DNMTs are viewed as an important epigenetic target for drug development. However, the impression of DNMTs on inflammation and cancer is still controversial, and therapeutic methods targeting DNMTs remain under exploration. Herein, this review mainly summarizes the findings on biological regulation of DNMTs as well as regulatory mechanisms and clinical applications of DNMTs in cancer and inflammation, and highlights several novel strategies for targeting DNMTs.